TAXPAYER’S FILING OF A RETURN ACKNOWLEDGING TAX DEBT CONSTITUTES THE TAX CREDIT AND DISPENSES WITH FURTHER ADMINISTRATIVE ACTION (CIPEEX, 2025)
This article analyzes the legal effects of a taxpayer’s filing of a return acknowledging a tax debt, arguing that such filing immediately constitutes the tax credit and dispenses with additional administrative steps, consistent with the Superior Court of Justice’s settled case law. The objective is to delineate the practical reach of this automatic constitution with respect to enforceability, enrollment in the registry of outstanding tax receivables, and collection mechanisms, while identifying safeguards for amended returns and for cases involving fraud, willful misconduct, or sham transactions. The study adopts a doctrinal and case-law approach, examining the National Tax Code, the Law on Tax Enforcement, and superior-court precedents, alongside administrative routines for monitoring and collection. The findings indicate that the debt acknowledgment embodied in the return authorizes, upon default, prompt enrollment in active debt and subsequent tax enforcement proceedings without the need for a supplementary assessment, thereby enhancing fiscal efficiency and procedural predictability; at the same time, the legal framework preserves the possibility of amendments within statutory limits and allows auditing where red flags arise. The conclusion is that this model combines simplification with taxpayer responsibility, fostering transparency and legal certainty in tax relations, provided it is paired with clear protocols for amendment, auditing, and proportionate enforcement.
Keywords: tax enforcement; enrollment in active debt; debt acknowledgment; self-assessment